The Effect of Laboratory Management Knowledge, Facility Contribution, Management Competence on the Effectiveness of LAB Utilization for Physics Learning Through the Implementation of Laboratory Management - Singerin, Sarlota (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the Effect of Laboratory Management Knowledge, Facility Contribution, Management Competence on the Effectiveness of LAB Utilization for Physics Learning Through the Implementation of Laboratory Management. This research is included in descriptive quantitative research. This research was conducted at SMPN 4 Malang. The sampling technique in this study was random sampling which was carried out on students in grades 1,2, and 3 so that in this study the sample obtained was 100 students of SMPN 4 Malang. The data analysis technique in this study used Partial Least Square (PLS). PLS is a Structural Equation Modelling (SEM) equation model with an approach based on variance or component-based structural equation modeling. The results showed that some variables show the effect while some do not. The future research that involves another place and other variables need to be conducted.